If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.60p = p + -32 Reorder the terms: 0.60p = -32 + p Solving 0.60p = -32 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. 0.60p + -1p = -32 + p + -1p Combine like terms: 0.60p + -1p = -0.4p -0.4p = -32 + p + -1p Combine like terms: p + -1p = 0 -0.4p = -32 + 0 -0.4p = -32 Divide each side by '-0.4'. p = 80 Simplifying p = 80
| 6m+8=80 | | 15=4y+x | | 6n-9=51 | | X=20+-4 | | 15=4x+y | | x+17.95=71.80 | | 3r+6*6=3r-1*5 | | 15=y+4x | | 8=8-4(x+1) | | 9k+1=3(3k-1) | | 14-4(w-7)=22 | | 8(x+1)=8 | | 4y+5=15 | | -21+-3= | | e=450-18920 | | ux+vy=wforx | | -2=y-9 | | 11+9j^2=15 | | 38x+36=5(x+2)*7x+4 | | x^3+10x^2-8x-40=0 | | B-3*5=3B | | xa+b=c | | 4a+9a=36 | | x-5=11-3x | | x+y-3z=29 | | 3(13-n)=15 | | 4[4-x+4]=12 | | -3=14x | | 1.50x+2.00(6)=1.80(x+6) | | 2(y-6)-y=-12+1 | | 11.98=15+(-9.8)(x) | | 2y+17=3y-10 |